2002
DOI: 10.1038/sj.onc.1206015
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent cell division cycles are driven by ectopic Cdk2, cyclin A/E and E2F activities

Abstract: Pluripotent cells of embryonic origin proliferate at unusually rapid rates and have a characteristic cell cycle structure with truncated gap phases. To define the molecular basis for this we have characterized the cell cycle control of murine embryonic stem cells and early primitive ectoderm-like cells. These cells display precocious Cdk2, cyclin A and cyclin E kinase activities that are conspicuously cell cycle independent. Suppression of Cdk2 activity significantly decreased cycling times of pluripotent cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
445
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(480 citation statements)
references
References 70 publications
32
445
2
1
Order By: Relevance
“…Interestingly, inhibition of Cdk2/Cyclin E activity in murine ESCs using a pharmacological inhibitor results in lengthening of the cell cycle over all phases consistent with the cell cycle-independent expression of Cdk2 and Cyclin E, without impact on expression of pluripotent markers such as Oct4 or Rex1 (Stead et al, 2002). CDK2 showed the highest kinase activity compared with other G1-specific CDKs (CDK4 and CDK6); we, therefore, hypothesised that CDK2 might play an important role in maintaining hESCs proliferation and pluripotency, and set out to investigate its function.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Interestingly, inhibition of Cdk2/Cyclin E activity in murine ESCs using a pharmacological inhibitor results in lengthening of the cell cycle over all phases consistent with the cell cycle-independent expression of Cdk2 and Cyclin E, without impact on expression of pluripotent markers such as Oct4 or Rex1 (Stead et al, 2002). CDK2 showed the highest kinase activity compared with other G1-specific CDKs (CDK4 and CDK6); we, therefore, hypothesised that CDK2 might play an important role in maintaining hESCs proliferation and pluripotency, and set out to investigate its function.…”
Section: Discussionmentioning
confidence: 62%
“…For collection of cells at the G1 stage of the cycle, cells were first treated by Nocodazole for 16 h, then the drug was removed by several washes with media and a fresh media supplemented with 10 mg/ml of aphidicholine (Sigma) was applied for the next 9-10 h as it was reported for mouse embryonic stem cells (Stead et al, 2002). To demonstrate that cells were properly released from blocking procedures, cell cycle progression was analysed after release from inhibitors (Supplementary Figure 2) at every 1-2 h. For example, cells that were blocked in G1 by application of nocodazole-aphidicholine block took 4-5 h to resume the normal cell cycle distribution (Supplementary Figure 2).…”
Section: Synchronization Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the case of cyclin B1, examples of cyclin E1 expression outside of the normal cell cycle phase have been reported in pluripotent murine embryonic cells (Stead et al, 2002) and in cells undergoing apoptosis (Mazumder et al, 2000). The cyclin E1 complex was active at 16 h after treatment, which was earlier than cyclin A or cyclin B1 complexes.…”
Section: Discussionmentioning
confidence: 80%
“…One of the explanations for the high aneuploidy rate in hESCs cells, compared with hiPSCs and controls, might lies in the possibility that ESCs guarantee rapid cell division by bypassing certain mechanisms of cell-cycle control and by that, enabling the survival of chromosomally aberrant cells. As it turns out, in early development, the strict requirements for cell growth are suspended to allow rapid cell proliferation 38,39 and is activated again when ESCs are induced to differentiate into embryoid bodies. 40,41 A recent study, conducted by Mayshar et al 34 , identified a substantial number of hiPS cell lines carrying full and partial chromosomal aberrations.…”
Section: Aneuploidy Screeningmentioning
confidence: 99%